Optimal doses of intranasal esketamine plus dexmedetomidine for sedating toddlers during transthoracic echocardiography: a prospective, double-blind, randomized trial - Dongjie Pei; Ting Xiao; Li Zeng; Siwei Wei; Lei Wang; Zhen Du; Shuangquan Qu (Annals of Medicine)
Introduction Esketamine has unique advantages in combination with dexmedetomidine for sedation in young children, owing to its sympathetic activity and mild respiratory depression. However, the optimal dose is yet to be determined. In this study, we compared the different doses of intranasal esketamine combined with dexmedetomidine for sedation during transthoracic echocardiography in toddlers.Patients and Methods A total of 121 eligible children aged 13 years, who were scheduled for transthoracic echocardiography were randomized into three groups. They were treated with intranasal dexmedetomidine 1 mcg.kg−1 + esketamine 0.5 mg.kg−1 (group S1), dexmedetomidine 1 mcg.kg−1 + esketamine 1 mg.kg−1 (group S2), or dexmedetomidine 1 mcg.kg−1 + esketamine 1.5 mg.kg−1 (group S3). The primary outcome was the success rate of sedation, other outcomes included HR, SpO2, onset time, wake-up time, and adverse effects.Results The success rate of sedation was significantly higher in groups S2 (85.4%) and S3 (87.5%) than ingroup S1 (60%) (p = 0.004). The baseline HR and SpO2 did not differ between the groups at the corresponding time points following drug administration. The onset time and duration of sedation in group S1 were significantly longer than those in groups S2 and S3 (p = 0.000). However, there were no differences in the wake-up time or adverse effects among the three groups.Conclusions Intranasal administration of 1 mg.kg−1 esketamine combined with 1 mcg.kg−1 dexmedetomidine provided satisfactory sedation in young children undergoing transthoracic echocardiography. This sedative approach offers a rapid onset of awakening with few side effects.Clinical trial registration number ChiCTR2200060976, 2022/06/14 (trail from August 2022 to January 2023)